The influence of Environmental, Social & Governance (ESG) risk rating on corporate financial risk in companies listed on IDX ESG leaders with board gender diversity as a moderating variable - Dunensa, Dina Lare; Baskara, I Gde Kajeng (International journal of economic perspectives, 2025)
This study analyzes the impact of Environmental, Social, and Governance (ESG) Risk Ratings on Corporate Financial Risk for companies listed on the IDX ESG Leaders index between 2020 and 2024. A quantitative research approach was employed, utilizing secondary data from the annual reports of companies listed on the Indonesia Stock Exchange (IDX). Data was collected through saturated sampling, including 30 companies from the IDX ESG Leaders for each year over the five-year observation period, resulting in a total of 150 samples. Moderated Regression Analysis (MRA) was applied to the data. The results demonstrate that the ESG Risk Rating has a significantly negative impact on Corporate Financial Risk. However, gender diversity does not exert a significant moderating influence on the relationship between Environmental, Social, and Governance (ESG) performance and corporate financial risk. These findings align with both stakeholder and signaling theories, indicating that firms with reasonable ESG performance exhibit lower total risk. The insights gained from this study will assist investors and portfolio managers in evaluating the influence of ESG and Board Gender Diversity on corporate financial risk, thereby facilitating improved investment decisions.